Neuroimaging Analysis of the Dopamine Basis for Apathetic Behaviors in an MPTP-Lesioned Primate Model. - LinLin Tian; Yuanxuan Xia; Hubert P Flores; Meghan C Campbell; Stephen M Moerlein; Joel S Perlmutter (PLoS ONE, 2015)
Apathy commonly occurs in Parkinson disease (PD) patients; however, the role of dopamine in the pathophysiology of apathy remains elusive. We previously demonstrated that dopaminergic dysfunction within the ventral tegmental area (VTA)-nucleus accumbens (NAcc) pathway contributes to the manifestation of apathetic behaviors in monkeys treated with the selective dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). We now extend these studies to identify dopaminergic dysfunction in cortical regions that correlate with development of apathetic behaviors. Specifically, we measured the effects of MPTP on monkeys' willingness to attempt goal directed behaviors, which is distinct from their ability to perform tasks. A total of 16 monkeys had baseline magnetic resonance imaging (MRI) and positron emission tomography (PET), using 6-[18F]fluorodopa (FD), [11C]dihydrotetrabenazine (DTBZ), and 2β-[11C]carbomethoxy-3β-(4-fluorophenyl)tropane (CFT). The monkeys received unilateral infusion of different doses of MPTP (0 - 0.31mg/kg) to produce a wide range of severity of motor parkinsonism. Eight weeks after MPTP, PET scans were repeated and animals were euthanized. Apathetic behavior and motor impairments were assessed blindly both pre- and post-MPTP infusion. Apathy scores were compared to in vitro and in vivo dopaminergic measures. Apathy scores increased following MPTP and correlated with PET measures of dopaminergic terminals (DTBZ or CFT) in dorsal lateral prefrontal cortex (DLPFC), ventromedial prefrontal cortex (VMPFC), and insular cortex (IC). Among all the cortical regions assessed, forward step-wise regression analyses indicated that only stereologic cell counts in VTA, and not counts in the substantia nigra (SN), predict dopamine transporter changes in IC. Our findings suggest that dopaminergic dysfunction within the VTA-IC pathway plays a role in the manifestation of apathetic behaviors in MPTP-lesioned primates.